Marine Invertebrates as Bioindicators of Heavy Metal Pollution - Chiarelli, Roberto; Roccheri, Maria Carmela (Scientific Research, 2014)
Atmosphere, earth and water compose the environment. The presence of heavy metals in the environment has grown because of their large employment in some industrial and agricultural activities. Although these metals are terrestrial products, they flow into the sea through effluents and sewage or are directly discharged from industries placed on the seawater front. It should be considered that metals concentrations vary widely according to different seawater latitudes and depths and can be strongly influenced by fresh water discharges from heavily polluted rivers. In this review recent studies on heavy metal pollution in marine ecosystems and their organisms will be presented. Metal speciation, bioaccumulation in biota, as well as abiotic and biotic factors affecting their bioavailability will be reviewed. Moreover, the use of bioindicator organisms for the biomonitoring of heavy metal toxicity and their ecological effects will be defined. Many marine invertebrate species fulfill the following criteria: Sensitivity to a wide range of chemicals (especially to heavy metals), cost-effectiveness for repeatable tests, readily interpretable biological consequences of pollution. Among the most important marine invertebrates used as bioindicators, the sea urchin embryo is one of the most suitable, especially to assess metal/heavy metal pollution.
Keywords: Pollution; Heavy Metals; Bioidicators; Marine Invertebrates; Sea Urchin Embryos